PENGARUH PENERAPAN MODEL ELICITING ACTIVITIES (MEAs) TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS SISWA - Muhammad Fatonah; Nursakiah (Almeera Education, 2023)
This study aims to determine whether there is an influence of Model Eliciting Activities (MEAs) on students' mathematical representation ability. This type of research is a quasi-experiment involving two groups that are given different treatments. The population of this study was grade XI students of SMA Islam Terpadu Wahdah Islamiyah Makassar and two classes were selected by cluster random sampling as research samples, namely class XI IPA 1 and XI IPA 2. Class XI IPA 1 as an experimental class taught using Model Eliciting Activities (MEAs), while class XI IPA 2 as a control class taught using conventional learning. The research instruments used were observation sheets for learning implementation, observation sheets on student activities, and tests on students' mathematical representation abilities. The data that has been collected using these instruments is analyzed using descriptive and inferential statistical techniques. The results of the descriptive analysis showed that: (1) students' mathematical representation ability after being taught using Model Eliciting Activities (MEAs) was in the less category, namely 34.5786 out of an ideal score of 100, (2) students' mathematical representation ability after being taught using conventional learning was in the low category, which was 8.7636 out of an ideal score of 100, (3) the increase in students' mathematical representation ability after being taught using Model Eliciting Activities (MEAs) is in the low category, which is 0.170, (4) the increase in students' mathematical representation ability after being taught using conventional learning is in the less category, which is 0.0669. The results of inferential statistical analysis show that: (1) with the Mann-Whitney Test test it can be said that there is a significant difference between the mathematical representation ability score parameters of grade XI science students taught using the Eliciting Aivities Model and the mathematical representation ability score parameters of grade XI science students taught using conventional learning, (2) with the Mann-Whitney Test test, it can be said that there is no significant difference between the parameter of increasing the mathematical representation ability of grade XI science students taught using the Eliciting Aivities Model and the parameter of increasing the mathematical representation ability of grade XI science students taught using conventional learning. From the results of this study, it can be concluded that there is no influence of Model Eliciting Activities (MEAs) on students' mathematical representation ability.